Identifikasi Penggunaan Obat Off-Label Pada PAsien Obstetri Dan Ginekologi Di Klinik Kehamilan Sehat Serpong - Humaira Fadhilah; Siti Mutoyah; Frida Kasumawati (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2022)
Off-label drugs are the use of drugs outside the indications approved by the authorized institutions, such as the Food Drug Administration (FDA) in America and the Food and Drug Supervisory Agency (BPOM) in Indonesia. The use of drugs in pregnancy requires special attention, because some drugs can cross the placenta, so there is a possibility that these drugs are teratogenic, namely causing defects in the fetus. The purpose of this study was to identify the use off-label drugs in Obstetrics and Gynecology patients at the Healthy Pregnancy Clinic in Serpong. This study is a descriptive study and data were taken retrospectively with a total population of 654 patients and obtained 248 samples. From 248 medical records that met the inclusion criteria, 66.13% of patients aged 26-35 years, 37.90% of 13-28 weeks of gestation, 93.04% of drugs prescribed with On label indications and 6.96% of drugs with off label indication. The most widely used off-label drugs were misoprostol as much as 51.52% as an inducer of uterine contractions, ondansetron 27.27% as a treatment for nausea and vomiting in pregnant patients and nifedipine as much as 21.21% as a tocolytic.